The Architecture of Attrition - Yerkes, Carolyn (Opus Incertum, 2025)
Monumental prints of sixteenth-century siege warfare defy easy categorization, as they picture the complex dynamics of mobile military societies. The sprawling encampments that surrounded city walls during extended sieges constituted a novel form of social organization, one that was reflected in the innovative responses of artists. Siege encampment prints connect architectural history to a constellation of related disciplines, including military history, urbanism, technology, and cartography. Monumental prints depicting the late military campaigns of Charles V, which saw the creation of some of the largest encampments ever assembled, provide a case study for considering the pervasive impact of siege warfare on all aspects of life. The goal of attrition was at the heart of all sieges, a strategy that relied on architecture to succeed. Examining encampment prints through the lens of architectural history demonstrates one of the many ways in which the field operates at the intersection of multiple disciplines.